Nigerian farmers' preferences on the timing of the purchase of rice, cowpea, and maize seeds - Takeshima, Hiroyuki; Nagarajan, Latha; Salau, Sheu; Oyekale, Abayomi (International Food Policy Research Institute, 2010)
Nigerian farmers have been slow in adopting improved seeds due to constraints in both supply and demand. Demand-side constraints pertain to farmers' characteristics, while supply-side constraints are related to capacity. Farmers' seed demand is complex, and empirical information on Nigerian farmers' seed demand is scarce. One of the less-studied issues is farmers' preference for obtaining seeds closer to planting time. Farmers often purchase seed around planting time, when seed prices tend to be higher. On the other hand, the formal seed sector, often constrained by capacity, distributes seed before or after planting time but not at planting time. Knowing whether farmers are willing to pay higher prices for seeds at planting time may provide useful information on whether the formal seed sector can significantly raise the adoption of improved seeds by ensuring their availability around this season. This study estimates the premium that farmers are willing to pay for seeds if they can buy the seeds one month closer to planting time, and how this premium varies across farmers with different income levels and specific crops (cowpea, rice, and maize).